The problems of conceptual – terminological apparatus in standard documents regulating production of fur - CHLEBNIKOVA Н.; OMELCHENKO Н. (Commodity science. Technologies. Engineering, 2010)
The article shows that simultaneous use of national and international standards is complicated by inconsistency of terminology in fur industry. The analysis carried out shows the difference of terms which must be taken into account during new standards development.